Contributions of the Simplified Competency Management Model to a Municipal Health Secretariat - Alessandro Albini; Aida Maris Peres; Maria de Lourdes de Almeida (Universidade de São Paulo, 2021)
Objective: to present the contributions of the Simplified Competency Management Model in a municipal health secretariat. Method: research of integrated mixed methods of exploratory-descriptive type. The model was applied in a southern Brazilian city, in the following stages: documentary, questionnaire, mapping of gaps and educational proposal. Results: in the first stage, after documentary research, a total of 14 general core competences were described and a questionnaire with specific core competences was chosen, with confirmation of correlation among them; in the second stage, the importance and expression competence at work degrees were obtained, after the questionnaires were filled out by 74 municipal public health managers; in the third one, a formula was adopted for the training priority degree and its classification; the fourth stage presented an educational proposal for the development of one of the competences with the highest priority degree. Conclusion: the model brings contributions by describing general core competences, after documentary research; carrying out the correlation between a questionnaire, containing specific core competences with the general ones; by mapping gaps; and by the proposal of learning trails for the development of competences.